German Packaging for Russian Novel: on the Problem of the Genre of the "Fiery Angel" by V. Bryusov - Eduard O. Krank (Publishing house "Sreda", 2021)
The article is devoted to the problem of the genre of V. Bryusov's novel "The Fiery Angel". The purpose of the article is to assert that the author uses the tradition of the medieval German novel in a stylized capacity. Bryusov needs the method of literary mystification not so much to hide relationships of real people who served as prototypes for the heroes of the novel, but to establish an allusive cultural connection between Germany in the era of M. Luther and the "Silver Age" of Russian literature, with its interest in issues of religion and gender. The relevance of the study dictated by the attention of the modern reader to the literature of the "Silver Age", as well as a special interest in metamorphoses that the novel genre undergoes in the era of modernism and postmodernism. The research materials are the text of the novel, biographical information related to the personalities of prototypes, reviews of literary criticism, as well as literary studies. We use descriptive, hermeneutic, synchronic, diachronic, historical-genetic, comparative, analytical and biographical methods in this work. The results of the study and their discussion consist in reflection on the paradigm in defining the genre of the novel, in pointing out the tradition of literary mystification, which rises to the "Belkin's Tales" by A. Pushkin. Also important is the circumstances that the religious searches inherent in the prototypes of the heroes of the novel are akin to Protestant moods of the Reformation. As a result, we conclude that the author, because of the anthropological unity of the archetypal situation, continued the literary tradition of the German Middle Ages. It is laid down in the basis of the plots of both V. Bryusov's novel and the first part of "Faust" by I.W. Goethe, as well as A. Belyi's novel "Petersburg", in which the love triangle invariant and its transformation from prototypes to characters is represented by the same mechanism as is characteristic of the "Fiery Angel". The assertion of this way of implementing a behavioral scheme (anthropological invariant) in the process of transforming prototypes into characters is the innovation of our work.